2017
DOI: 10.3389/fcimb.2017.00261
|View full text |Cite
|
Sign up to set email alerts
|

Th2/1 Hybrid Cells Occurring in Murine and Human Strongyloidiasis Share Effector Functions of Th1 Cells

Abstract: Infections by the soil-transmitted threadworm Strongyloides stercoralis affect 30–100 million people worldwide, predominantly in tropic and sub-tropic regions. Here we assessed the T helper cell phenotypes in threadworm-infected patients and experimental murine infections with focus on CD4+ T cells co-expressing markers of Th2 and Th1 differentiation. We show that mice infected with the close relative S. ratti generate strong Th2 responses characterized by the expansion of CD4+ GATA-3+ cells expressing IL-4/-5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 55 publications
1
11
0
1
Order By: Relevance
“…Calculating the ratios of Th2 cells to Treg based on their frequencies in CD4 + T cells, we found significantly elevated Th2 effector to Treg ratios in the small intestine of infected GF compared to SPF mice (Figure 5C ). We have previously shown that intestinal nematode infections lead to the differentiation of GATA-3 + Th2 and GATA-3 + T-bet + Th2/1 hybrid cells ( 51 , 52 ). Th2/1 cells developed in infected SPF as well as GF mic, hence microbial signals were dispensable for their induction (Figures 5D,E ).…”
Section: Resultsmentioning
confidence: 99%
“…Calculating the ratios of Th2 cells to Treg based on their frequencies in CD4 + T cells, we found significantly elevated Th2 effector to Treg ratios in the small intestine of infected GF compared to SPF mice (Figure 5C ). We have previously shown that intestinal nematode infections lead to the differentiation of GATA-3 + Th2 and GATA-3 + T-bet + Th2/1 hybrid cells ( 51 , 52 ). Th2/1 cells developed in infected SPF as well as GF mic, hence microbial signals were dispensable for their induction (Figures 5D,E ).…”
Section: Resultsmentioning
confidence: 99%
“…The Th2 cells have been reported to further develop into Th9 cells ( Veldhoen et al, 2008 ). More complexity in T cell differentiation was observed in the form of co-expression of mutually exclusive lineage-specifying transcription factors (TFs) ( Peine et al, 2013 ; Bock et al, 2017 ). This co-expression can lead to the development of stable or intermediate subtypes that share characteristics of more than one type of T cell ( Tartar et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Effective lineage commitment is enforced by positive feedback mechanisms and reciprocal inhibition of the opposing developmental program, suggesting that Th2 and Th1 differentiation are mutually exclusive . However, many CD4 + T cells activated in helminth infections acquire a Th2/1 hybrid phenotype in stably coexpressing GATA‐3/T‐bet and Th2 cytokines with IFN‐γ . Th2/1 cells display lower immunopathological potential than Th1 or Th2 cells and are detectable in nematode‐infected humans .…”
Section: Introductionmentioning
confidence: 99%
“…However, many CD4 + T cells activated in helminth infections acquire a Th2/1 hybrid phenotype in stably coexpressing GATA‐3/T‐bet and Th2 cytokines with IFN‐γ . Th2/1 cells display lower immunopathological potential than Th1 or Th2 cells and are detectable in nematode‐infected humans .…”
Section: Introductionmentioning
confidence: 99%